2006
DOI: 10.1007/s00264-006-0109-8
|View full text |Cite
|
Sign up to set email alerts
|

Autologous blood transfusion following total knee arthroplasty: is it always necessary?

Abstract: A retrospective study of 85 patients undergoing primary total knee replacement (TKR), who also received autologous blood transfusion (ABT) to compensate for the perioperative blood loss. In our series 16.4% of the patients needed allogenic blood transfusion. Of the remaining 83.4% only 49.5% received autologous transfusion. Autologous transfusion was withheld in 34.1% of cases either because the blood volume was inadequate or because the collection time exceeded the recommended time limit. The mean haemoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…8,9 Numerous authors have found that autologous reinfusion drains are both effective and beneficial in reducing postoperative need for allogeneic transfusions. [10][11][12][13][14][15][16] However, concerns about dilutional coagulopathy, disseminated intravascular coagulation, reinfusion of anticoagulants, cardiovascular complications, and renal insufficiency after transfusion of shed blood during TKA have been raised. [17][18][19][20] In addition, the hematocrit of the reinfused blood may not be optimal to raise the hemoglobin level in the postoperative period.…”
Section: Blood Salvage Systemsmentioning
confidence: 99%
“…8,9 Numerous authors have found that autologous reinfusion drains are both effective and beneficial in reducing postoperative need for allogeneic transfusions. [10][11][12][13][14][15][16] However, concerns about dilutional coagulopathy, disseminated intravascular coagulation, reinfusion of anticoagulants, cardiovascular complications, and renal insufficiency after transfusion of shed blood during TKA have been raised. [17][18][19][20] In addition, the hematocrit of the reinfused blood may not be optimal to raise the hemoglobin level in the postoperative period.…”
Section: Blood Salvage Systemsmentioning
confidence: 99%
“…The literature includes various reports about postoperative autologous drainage blood reinfusion in TKA 3-9 . Some researchers have reported that postoperative autologous drainage blood reinfusion offered no advantage in relieving the decrease in hemoglobin levels and reducing the volume of allogeneic blood transfusion; rather, these studies reported that this procedure simply increased the cost of TKA 3 , 4 , 6 . However, some researchers have drawn contradictory conclusions 5 ,.…”
Section: Discussionmentioning
confidence: 99%
“…Blood loss after TKA is mainly due to the application of a pneumatic tourniquet in TKA, and controlling this problem is essential. Two methods, drainage blood reinfusion and temporary clamping drainage, have been developed to protect against postoperative bleeding after TKA, but there has been considerable debate regarding their therapeutic effects 2-19 . Moreover, most of the studies evaluating the effects of the two methods on the volumes of blood loss and allogeneic blood transfusion were performed in patients with osteoarthritis (OA).…”
Section: Introductionmentioning
confidence: 99%
“…The basic principle is to retrieve the shed blood and to reinfuse it to the patient (washed or unwashed) in the postoperative period. [39][40][41][42][43][44][45] Various authors have reported on the efficacy and the beneficial effect of autologous transfusion in reducing the postoperative need for allogeneic transfusion. [41][42][43][44][45] Shenolikar et al, in a prospective randomized study, evaluated the impact of cell salvage in reducing allogeneic blood transfusion requirements in 100 TKAs.…”
Section: Intraoperative Blood Salvage Systemsmentioning
confidence: 99%
“…[39][40][41][42][43][44][45] Various authors have reported on the efficacy and the beneficial effect of autologous transfusion in reducing the postoperative need for allogeneic transfusion. [41][42][43][44][45] Shenolikar et al, in a prospective randomized study, evaluated the impact of cell salvage in reducing allogeneic blood transfusion requirements in 100 TKAs. 46 The authors found that the cell saver group (n ¼ 50) had a lower incidence of allogeneic blood transfusion (16%) than the control group (80%).…”
Section: Intraoperative Blood Salvage Systemsmentioning
confidence: 99%